Strategies to implement a continuous improvement plan in the ABET accredited mining engineering program - (:unkn) unknown (LACCEI (Latin American and Caribbean Consortium of Engineering Institutions), 2024)
The process of accrediting an academic program is in many cases cumbersome. However, in many cases after obtaining the accreditation, the implementation of continuous improvement plans is even more difficult. Especially because the students, who are one ...
Keywords: Mejora continua; Ingeniería de minas